Pengembangan Teks Eksplanasi sebagai Bahan Ajaran Melalui Pendekatan Genre Expository dengan Media Visual di Kelas XI SMA - Meily Indriani; Liesna Andriany; Deliani; Ratna Soraya; Nila Safina (Medan Resource Center, 2021)
This study aimed to develop an expository writing text module with an expository genre approach. The study used the 4D research and development method by Thiagarajan. The stages of this research method arecarried out at the stage of defining, designing, and developing without conducting the dissemination stage. The data consisted of primary and secondary data. The secondary data were taken from articles from relevant previous studies, and books. While the primary data are taken directly from expertsin the formo fan assessment of teaching material products. The study used the documentation techniques. The study used questionnaire to collect data. Then the collected data will be analyzed byusing the data analysis technique of Miles and Huberman. Through the assessmen to material experts, the resulting module received a final score of 3.88 as very validcriteria, and the overall average score of the product design assessment by design experts was 3.67 as very valid criteria. Based on these results, it is concluded that the prototype of the explanatory text writing module with visual media developed is valid and feasible to be tested for the next stage, namely the dissemination stage.